Legal Protection for Landowners in Forest Areas Utilized for Plantation Activities (Case Study: Supreme Court Decision Number 2929 K/PDT/2017) - Nafisa Verlee Ameeralia; Wardani Rizkianti (Green Publisher Indonesia, 2025)
Land ownership that has been legally recognized is entitled to legal certainty and protection. However, there is an issue where landowners do not receive legal protection as reflected in Supreme Court Decision Number 2929 K/Pdt/2017. The purpose of this study is to examine the application of legal rules for landowners in forest areas and the legal protection afforded to landowners in forest areas used for plantations, based on the judicial considerations in Supreme Court Decision Number 2929 K/Pdt/2017. This article employs normative legal research methods with a statutory and case approach. The research questions addressed in this article are the application of legal rules for landowners in forest areas and the legal protection of landowners in forest areas used for plantations, based on the judicial considerations in Supreme Court Decision Number 2929 K/Pdt/2017. The study concludes that Presidential Regulation No. 88 of 2017 serves as a reference for the application of legal rules for landowners in forest areas. Furthermore, the case in Supreme Court Decision Number 2929 K/Pdt/2017 did not take into account the fact that the Respondent in Cassation conducted business activities without holding a Right to Cultivate (HGU), resulting in losses for the landowners. Landowners should be granted legal protection, as the Respondent in Cassation lacked an HGU, which clearly violates legal provisions.